Model Pelayanan Pastoral Konseling Kristen: Remaja Kecanduan Game Online - Naek Tua Parlindungan; Rio Janto Pardede (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2022)
Counseling for teenagers who are addicted to online games is a service that must be seriously considered by Christian mentors, because through this service and guidance it is hoped that teenagers can be free from dependence and can live as teenagers who are useful for society, nation and state, especially to God. The purpose of this study was to analyze the model of pastoral counseling services to adolescents who are addicted to online games. The research model used is a descriptive model with a qualitative approach, with data collection through interviews with teenage students in three Christian schools in Batu Tourism City. From the data studied, it shows that the problem of online game in adolescents is not an ordinary problem, therefore the school and counseling teachers must pay special, in-depth and focused attention in order to solve adolescent problems. The results of these findings present to: (1) the school or the leadership of the school foundation should provide and apply consistently concerning youth spirituality. (2) the counseling guidance teachers should continue to equip themselves with material deepening and seminars in order to increase their knowledge and prepare themselves in dealing with adolescent problems. (3) counseling guidance teachers should apply new pastoral counseling models such as thegame/game model and the cooperative stepping model that is effective and in accordance with the context of teenagers in Batu Tourism City in order to deal with the problem of online game.